Dendritic Cell Cancer Therapy: Vaccinating the Right Patient at the Right Time - van Willigen, Wouter W.; Bloemendal, Martine; Gerritsen, Winald R.; Schreibelt, Gerty; de Vries, I. Jolanda M.; Bol, Kalijn F. (Frontiers in Immunology, 2018)
Immune checkpoint inhibitors propelled the field of oncology with clinical responses in many different tumor types. Superior overall survival over chemotherapy has been reported in various metastatic cancers. Furthermore, prolonged disease-free and overall survival have been reported in the adjuvant treatment of stage III melanoma. Unfortunately, a substantial portion of patients do not obtain a durable response. Therefore, additional strategies for the treatment of cancer are still warranted. One of the numerous options is dendritic cell vaccination, which employs the central role of dendritic cells in activating the innate and adaptive immune system. Over the years, dendritic cell vaccination was shown to be able to induce an immunologic response, to increase the number of tumor infiltrating lymphocytes and to provide overall survival benefit for at least a selection of patients in phase II studies. However, with the success of immune checkpoint inhibition in several malignancies and considering the plethora of other treatment modalities being developed, it is of utmost importance to delineate the position of dendritic cell therapy in the treatment landscape of cancer. In this review, we address some key questions regarding the integration of dendritic cell vaccination in future cancer treatment paradigms.